Pengembangan Kriteria Seleksi untuk Perakitan Terung (Solanum melongena L.) Berdaya Hasil Tinggi - Putri, Faradila Danasworo; ,, Sobir; Syukur, Muhamad; Maharijaya, dan Awang (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Eggplants (Solanum melongena L.) are consumed worldwide in a variety of colors, shapes and sizes, thus vegetable plant breeders place great interest in developing high yielding genotypes in response to the population growth and the need to increase vegetable production. This research was aimed to determine the proper character as selection character for breeding high yielding eggplants by using estimated heritability value, coefficient of genetic diversity, characters correlation and path analysis. The experiment was conducted during 2014 to August 2015 at Cikabayan Experimental Field, Tajur Experimental Field and Pasir Sarongge Experimental Field, IPB, West Java. A total of 12 characters was observed in the 25 genotypes. Eleven characters has a high estimated heritability value and high coefficient of genetic diversity value. Those characters were time of flowering, time of harvest, fruit length, fruit weight, fruit diameter, plant height, stem length, fruit apical scar length, calyx length, the number of fruits per plant and fruit weight per plant. Results of correlation and path analysis showed that fruit length, fruit weight, fruit diameter, stem diameter, calyx length and number of fruits per plant have a direct positive effect on fruit weight per plant. Fruit weight, fruit diameter and number of fruits per plant are suitable characters in determining the selection criteria for developing high productivity eggplant.Keywords: path analysis, correlation, heritability, genetic diversity coefficient